2011
DOI: 10.1111/j.1755-0998.2011.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR enrichment techniques to identify the diet of predators

Abstract: The increasing sensitivity of PCR has meant that in the last two decades PCR has emerged as a major tool in diet studies, enabling us to refine our understanding of trophic links and to elucidate the diets of predators whose prey is as yet uncharacterized. The achievements and methods of PCR-based diet studies have been reviewed several times, but here we review an important development in the field: the use of PCR enrichment techniques to promote the amplification of prey DNA over that of the predator. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 107 publications
(250 reference statements)
2
67
0
Order By: Relevance
“…What is evident is that the number of studies using DNA barcodes in constructing nodes and links in aquatic food webs is currently increasing, and that the development of methods is picking up speed (e.g., for recent papers of methods involving blocking primers, see O'Rorke et al 2012a;Leray et al 2013; for improved quantifications, see Thomas et al 2014). Thus, we expect the next few years to bring studies where DNA barcodes have been applied simultaneously to resolve the nodes and the links of "full" aquatic food webs (or substantial parts of them).…”
Section: Reconstructing Larger Modules Within Aquatic Websmentioning
confidence: 99%
“…What is evident is that the number of studies using DNA barcodes in constructing nodes and links in aquatic food webs is currently increasing, and that the development of methods is picking up speed (e.g., for recent papers of methods involving blocking primers, see O'Rorke et al 2012a;Leray et al 2013; for improved quantifications, see Thomas et al 2014). Thus, we expect the next few years to bring studies where DNA barcodes have been applied simultaneously to resolve the nodes and the links of "full" aquatic food webs (or substantial parts of them).…”
Section: Reconstructing Larger Modules Within Aquatic Websmentioning
confidence: 99%
“…The specificity and sensitivity tests revealed that all primer combinations were appropriate for molecular detection of predation under laboratory conditions (O'Rorke et al, 2012). However, it was also necessary to test their reliability under real conditions of digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The reliable identification of a prey species requires that only prey DNA sequences are detected. The design of species-specific primers is therefore essential (O'Rorke et al, 2012). Since digestion of the prey results in degradation of its DNA, the mitochondrial cytochrome oxidase I (COI) gene appears as a suitable target for amplification because there are several copies of the gene per organelle and also several organelles per cell.…”
Section: Introductionmentioning
confidence: 99%
“…A review of phyllosoma diets strongly suggested that gelatinous zooplankton and some small crustaceans are their main prey, and that there are pronounced changes in diet between mid and late stages (Jeffs 2007). Current research at the LML using polymerase chain reaction (PCR) enrichment techniques may identify prey species (O'Rorke et al 2012). Late-stage phyllosomes accumulate large amounts of lipid, which appears important for fuelling the non-feeding puerulus stage that vigorously swims inshore to settle on coastal reefs 1Á2 years after hatching (Jeffs & Holland 2000;Jeffs et al 2001a, b;Wells et al 2001;Jeffs 2007).…”
Section: Reproductionmentioning
confidence: 99%